2017
DOI: 10.1177/0025817217703520
|View full text |Cite
|
Sign up to set email alerts
|

Toxic megacolon as a rare complication following atropine therapy due to organophosphate poisoning: A case report

Abstract: The main therapeutic basis for a case of organophosphate poisoning is a combination therapy which includes atropine as an anticholinergic drug and pralidoxime. If the poisoning is severe, a high dose of this combination of medicines may be needed, but this may cause serious side effects: paralytic ileus or even megacolon; however, these gastrointestinal events are very rare. Here, we report a case of organophosphate poisoning where atropine therapy was given and led to drug-associated toxic megacolon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In summary, these are the recommended indications to delay EN [11][12][13] . In addition, fearing of ileus caused by atropine might be one of the reasons of previously reported cases 6,8,9,21) . Moses et al 10) reported that atropinization precludes early EN because of atropine' s effect on gut motility, indicating possible mucosal injuries due to organophosphate and carbamate can be another reason not to start EN during atropinization 1,2) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, these are the recommended indications to delay EN [11][12][13] . In addition, fearing of ileus caused by atropine might be one of the reasons of previously reported cases 6,8,9,21) . Moses et al 10) reported that atropinization precludes early EN because of atropine' s effect on gut motility, indicating possible mucosal injuries due to organophosphate and carbamate can be another reason not to start EN during atropinization 1,2) .…”
Section: Discussionmentioning
confidence: 98%
“…A previous study reported that atropine delayed gastric emptying resulting in delayed mouth-to-ileum transit 6) . However, cases of ileus are rarely reported in commonly used dosages 8,9,21) . In addition, ileus might not be a critical complication of atropine.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic megacolon developed form atropine intoxication: though incidence of atropine-associated toxic megacolon is very rare, however still few cases have reported such complication. These case reports suggested an involvement of atropine in the manifestation of toxic megacolon, (Mostafazadeh et al, 2017;Scharer et al, 1964;Mann et al, 1977). In the fi rst two cases, toxic megacolon developed after the administration of anticholinergic agent and was reversed after the discontinuation of the anticholinergic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiological bases of atropine involvement in toxic megacolon remain unclear, some theories suggest that anticholinergic agents, such as atropine, lead to gastrointestinal peristalsis inactivity and delay intestinal transit time which in turn may have caused toxic megacolon. (Mostafazadeh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…, an acute gastric lesion shown in Figure 1 . Gastroscopy showed that there were many bulges in the mucosa of the stomach cavity, purulent secretions at the top, and obvious congestion in the surrounding mucosa (Figure 1B ), and edema in part of the descending duodenum (Figure 1C ); (2) Atropine, which was administered against poisoning, inhibited intestinal peristalsis and promoted the absorption of intestinal edema and toxins, further leading to an increased abdominal pressure (maximum: 27 cm H 2 O) and weakened bowel sounds[ 8 ]; (3) Severe poisoning caused serious hemodynamic changes and hypoxia. The concentration of lactic acid was 13.0 mmol/L, and therefore, a high dose of norepinephrine was administered to maintain blood pressure.…”
Section: Discussionmentioning
confidence: 99%